Structural change and productivity growth in India and the People's Republic of China - Jagannath Mallick (Asian Development Bank Institute (ADBI), 2017)
Globalization has significantly changed the composition and structure of emerging economies, which has in turn reallocated factors across various economic activities. In this context, this study examines the sources of labor reallocation or structural change, and measures and empirically evaluates the contribution of structural change to labor productivity growth (LPG) by controlling for indicators of economic globalization and types of human capital. The study also evaluates the relative contributions of human and physical capital to LPG. The study found that changing final demand is the most crucial factor in labor reallocation in India. In the PRC, this and changes in technology are factors of labor allocation. The regression analysis confirmed that structural change, globalization, and human capital significantly contribute to LPG. Due to its prevailing structure, India is capable of leading global economic growth in the future, provided that certain necessary policies on human capital development, outward-oriented policies, and other conducive economic reform measures are taken.
Keywords: F1; J2; O4; 330; Economics; Industry and trade; China; People's Republic of